Comparing plasma levels and ratios of tryptophan, serotonin, kynurenine and quinolinic acid between patients with bipolar disorder and healthy controls: impact of depressive episode or post-traumatic stress disorder symptoms - Dell’Oste, Valerio; Palego, Lionella; Bordacchini, Andrea; Rimoldi, Berenice; Parrini, Livia; Pedrinelli, Virginia; Giannaccini, Gino; Betti, Laura; Carmassi, Claudia (Frontiers in Psychiatry, 2026)
BackgroundBipolar disorder (BD) is a chronic mental illness displaying recurrent episodes of impaired mood, in alternance with euthymic or subsyndromal periods. The comorbidity between BD and post-traumatic stress disorder (PTSD) is attracting attention due to its frequency, diagnostic difficulties, and worsening prognosis. Consequently, identifying molecular substrates of post-traumatic vs. depressive symptoms in BD would provide much benefit for patients’ rescue. This study thus focused on tryptophan (TRP) metabolism, at the crossroad between neurotransmission, immunity and inflammation, under distinct BD mental conditions.MethodsWe compared plasma TRP, serotonin (5-HT), kynurenine (KYN) and quinolinic acid (QUIN) among 20 euthymic-BD patients with PTSD (PTSD group) or 20 with depressive episode (DEP group) and 24 controls (CTL group). Metabolic ratios were calculated to monitor TRP-path fluxes. All participants underwent clinical examinations by psychometric instruments as the: Structured Clinical Interview for DSM-5 disorders (SCID-5), Hamilton Depression Rating Scale (HAM-D), Young Mania Rating Scale (YMRS), Impact of Event Scale-Revised (IES-R), Mood Spectrum-Self-Report lifetime version (MOODS-SR), Trauma and Loss Spectrum-Self Report lifetime version (TALS-SR), Work and Social Adjustment Scale (WSAS). Blood withdraws were also achieved, followed by plasma measurements through ELISA.ResultsBoth DEP and PTSD-groups revealed markedly lower 5-HT and 5-HT/TRP values than controls, with additionally decreased 5-HT in DEP- vs. PTSD-subjects. DEP-patients also showed reduced TRP and increased QUIN, KYN and QUIN ratios vs controls, while PTSD-subjects displaying only increased QUIN/KYN values. Additionally, several correlations between biochemical and clinical parameters were reported. Noteworthy, 5-HT and 5-HT/TRP were negatively correlated with all psychometric measures, while all biochemical parameters studied, except KYN, were correlated with poor socio-personal functioning; otherwise, KYN-shunt parameters better distinguished the severity of DEP symptoms than the PTSD ones.ConclusionsSubstantially, BD-patients with low 5-HT and severe burden could be distinguished based on KYN profiles/trajectories when affected by depression or PTSD, entailing different neuroinflammatory/neuroendocrine patterns in mood vs. post-traumatic stress dimensions. This will encourage deeper assessment of BD metabolic/inflammatory biomarkers, allowing for refined patients’ stratifications and targeted therapeutic interventions.